Factors affecting the financial performance of Vietnamese joint-stock commercial banks - Truong, Đinh Ngọc Mai (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
This study examines the factors affecting the financial performance of commercial banks in Vietnam during the period 2015–2023. By combining macroeconomic variables and bankspecific variables, the study employs multiple regression models to explore their impact on financial indicators such as ROA, ROE, and NIM. The results show that the debt-to-equity ratio has a positive impact on ROA and NIM, indicating that financial leverage helps banks increase profitability. However, this ratio is not significant for ROE. Bank size also has a significantly positive effect on ROA, ROE, and NIM, confirming that larger banks can better optimize their resources. Conversely, the non-performing loan ratio has a strong negative impact on ROA and ROE, while it does not significantly affect NIM. This suggests that bad debts reduce banks’ profitability but have little impact on the net interest margin. Finally, bank age has a negative but insignificant impact on ROA and NIM, indicating that older banks may face challenges in innovation and performance optimization. Macroeconomic factors such as GDP and inflation are not statistically significant in any of the three models, suggesting that they do not have a substantial impact on the financial performance of banks during the study period.